2022
DOI: 10.7717/peerj.14235
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of immunoglobulin E as a biomarker for the diagnosis of acute ischemic stroke with carotid atherosclerotic plaques

Abstract: Objective In this study, serum markers of acute ischemic stroke (AICS) with carotid artery plaque were retrospectively evaluated to establish a basis for discovering serological indicators for early warning of acute ischemic stroke (AICS). Methods A total of 248 patients with AICS were enrolled in Lanzhou University Second Hospital from January 2019 to December 2020. The study population included 136 males and 112 females, 64 ± 11 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…In line with this, atopic patients with no sign of atherosclerosis with higher IgE levels had notably lower coronary flow reserve (CFR) which is used as an endothelial dysfunction biomarker [ 56 ]. In another study, higher levels of serum IgE levels were found in patients with acute ischemic stroke [ 57 ]. Moreover, an association between higher IgE levels with cardiovascular mortality was reported [ 58 ].…”
Section: Engaged MC Expressed Receptors In Atherosclerosismentioning
confidence: 99%
“…In line with this, atopic patients with no sign of atherosclerosis with higher IgE levels had notably lower coronary flow reserve (CFR) which is used as an endothelial dysfunction biomarker [ 56 ]. In another study, higher levels of serum IgE levels were found in patients with acute ischemic stroke [ 57 ]. Moreover, an association between higher IgE levels with cardiovascular mortality was reported [ 58 ].…”
Section: Engaged MC Expressed Receptors In Atherosclerosismentioning
confidence: 99%